Produk Layanan Jasa Lembaga Keuangan Keuangan Syariah dengan Akad Wakalah dan Rahn - Luthfiah Luthfiah (Lembaga Pengembangan Kinerja Dosen, 2025)
Sharia financial institutions continue to develop along with increasing public demand for services that comply with sharia principles. Among the various products offered, the Wakalah and Rahn contracts are two important instruments in providing diverse and flexible services. The Wakalah contract, which is a form of representation in transactions, allows customers to appoint a financial institution as a representative in managing their financial affairs. Meanwhile, the Rahn contract, or sharia pawn, allows customers to obtain financing by handing over goods as collateral. This research aims to explore the implementation and benefits of service products in sharia financial institutions that use Wakalah and Rahn contracts. The method used is literature study and case analysis of several sharia financial institutions in Indonesia. The research results show that the use of Wakalah and Rahn contracts not only increases flexibility and security for customers, but also supports the growth and stability of Islamic financial institutions. In addition, products based on these two contracts have been proven to be able to meet the diverse financial needs of society, while maintaining compliance with sharia principles. Thus, the integration of Wakalah and Rahn contracts in service products at sharia financial institutions is an effective strategy in supporting financial inclusion and sustainable economic development.